1998
DOI: 10.1007/bf02484622
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of prostaglandin D2 against the proliferation of human colon cancer cell lines and hepatic metastasis from colorectal cancer

Abstract: The inhibitory action of prostaglandin D2 (PGD2) and its effect on the cell cycle were examined in cell lines SW480 and LS174T of human colon cancer. The growth of the cell lines were assessed 24 h and 48 h after the addition of 1.0 microgram/ml and 10.0 micrograms/ml PGD2. The growth of SW480 cells was inhibited 48 h, but not 24 h, after the addition of 1.0 microgram/ml, and 24 h and 48 h after the addition of 10.0 micrograms/ml, while that of LS174T was inhibited by both doses after 24 h and 48 h. S-Phase DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…TXA 2 is involved in angiogenesis and subsequent development of tumor metastases, while PGI 2 displayed anti-cancerogenic effects in a murine cell model [4,25]. The DP receptor has been linked to inflammation which may represent a prestage to cancer, where DP1 shows anti-inflammatory effects and DP2 pro-inflammatory actions [26], although PGD 2 displayed anti-proliferative activity in-vitro [27]. Table V).…”
Section: Discussionmentioning
confidence: 99%
“…TXA 2 is involved in angiogenesis and subsequent development of tumor metastases, while PGI 2 displayed anti-cancerogenic effects in a murine cell model [4,25]. The DP receptor has been linked to inflammation which may represent a prestage to cancer, where DP1 shows anti-inflammatory effects and DP2 pro-inflammatory actions [26], although PGD 2 displayed anti-proliferative activity in-vitro [27]. Table V).…”
Section: Discussionmentioning
confidence: 99%
“…3. PGD 2 treatment inhibited proliferation in colorectal tumor cell lines, an effect which was associated with cell-cycle arrest [97]. However, a later study demonstrated that both PGJ 2 and 15d-PGJ 2 (the metabolites of PGD 2 ) induced proliferation of colorectal cancer cells [98], suggesting a role for these prostanoid metabolites in tumor cell survival.…”
Section: Eicosanoid Expression and Cell Proliferation In Colorectal Cmentioning
confidence: 99%
“…The synthesis of prostanoids is mediated by COX-1 and COX-2, and the latter enzyme frequently is induced in response to inflammatory stimulators, lysolecithin, and cytokines in order to produce prostanoids [26,27,28]. Prostanoids and COX enzymes have also been shown to associate with carcinogenesis in various tumors, including gallbladder carcinoma [29,30,31,32,33,34]. Gallbladder carcinoma and colon carcinoma have several analogous characteristics: (1) important association with inflammatory diseases, cholecystitis, and inflammatory bowel diseases; (2) a high incidence of polypoid lesion; and (3) increased COX enzymes in lesion and a therapeutic action of NSAIDs.…”
Section: Cholecystitis and Malignant Lesionsmentioning
confidence: 99%